Pengaruh Model Blended Learning terhadap Kemampuan Creative Thingking pada Peserta Didik SMA - Diana Silfiani Putri; Jujun Ratnasari; Billiyardi Ramdhan (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: This study aims to determine the effect of the blended learning model on the creative thinking ability of high school students on biotechnology materials at SMA N 1 Sukaraja, Sukabumi Regency. Methods: The method used in this study is a quasi-experimenal research design, namely the Non-equivalent Control Group Design. The sampling technique used was purposive sampling. The research instrument used was an uraian test with 8 questions integrated with 5 indicators of creative thinking ability (Fluency, Flexibility, problem sensitivity, Originality, and Elaboration). Results: In testing the hypothesis using the independent sig (2-tailed) test is 0.00 < 0.05, then Ho is rejected. So use of the blended learning model on the creative thinking abilities help in the learning process to improve creative thinking in the learning process in the classroom. Conclusion: It can be concluded that there is an effect on the use of the blended learning model on the creative thinking abilities of class XII students on biotechnology materials at SMA Negeri 1 Sukaraja.